2023
DOI: 10.1115/1.4056052
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Non-Intrusive Imaging Technique to Quantify Shrinkage of Elephant Foot Yam During Convective Drying

Abstract: Many countries are facing the problem of food wastage due to a lack of proper processing, preservation, and storage space and/or methods, which can be very effectively addressed using food drying techniques. The current work discusses the design and development of a novel convective drying system which predicts both the drying and the shrinkage characteristics of any food material simultaneously at different drying air velocities and temperatures. In the present work, the shrinkage characteristics of a cylindr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Similar phenomena have been observed in jujube slices dried using hot air drying, in which high temperatures lead to significant volume shrinkage [28]. Singh et al also reported that increasing the drying temperature resulted in an increased shrinkage of Elephant Foot Yam at the same final moisture content [29].…”
Section: Shrinkage Ratio and Rehydration Ratiosupporting
confidence: 60%
“…Similar phenomena have been observed in jujube slices dried using hot air drying, in which high temperatures lead to significant volume shrinkage [28]. Singh et al also reported that increasing the drying temperature resulted in an increased shrinkage of Elephant Foot Yam at the same final moisture content [29].…”
Section: Shrinkage Ratio and Rehydration Ratiosupporting
confidence: 60%
“…A rehydration study is required for identifying the quantum of damage in the structure of food during drying, which overall affects the rehydration characteristics of foods (Liu et al, 2021 ). The swelling of the food material and imbibing of water into dehydrated food takes place during rehydration along with the leaching of soluble solutes from the food (Sagar et al, 2018 ; Singh et al, 2022 ). The quality always remains a major concern along with energy conservation for optimizing any dehydration process (Zhang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%